Understanding Trademark Likelihood of Confusion: Unfair Competition in a Digital Era - Nukri Jintcharadze (European Scientific Journal, ESJ, 2024)
The development of the digital economy have increased risks of unfair competition using inappropriate or obviously false advertising of trademarks through social media. This, however, has erased legal ambiguity regarding the assessment of comparators of the trademarks before confusion for establishing unfair competition through the social networks. The paper distributes comparative research on distinguishing “legal name" and "commercial name” of trademarks before confusion when used for advertising purposes. While legal name is less relevant for the consumer, the commercial name under which undertaking operates on the market is a crucial element for establishing unfair competition. Accordingly, the paper through analytical research focuses on examining the rule of necessity of the cumulative presence of three established comparators: visual, phonetic, and semantic. Also, confusion between trademarks through the prism of unfair competition legislation can arise even without the presence of all these elements. The article provides suggestions to redefine legislative connotations of legal name and commercial name in respective statutory acts. It also recommends amending the notion of misleading commercial practice in Directive 2005/29/EC as the presence of the likelihood of one of the comparator autonomously creates confusion with any products, trademarks, trade names or other distinguishing marks of a competitor. As for Directive 2006/114/EC, it should be determined that in cases of misleading and comparative advertising, confusion may arise due to the presence of the likelihood of one of the comparators solely.